The Toxicity of our City: The Effect of Toxic Workplace Environment on Employee’s Performance - M. Ikhwan Maulana Haeruddin; Abdi Akbar; Tenri SP Dipoatmodjo; Agung Widhi Kurniawan; Rahmat Riwayat Abadi (Universitas Pendidikan Ganesha, 2022)
In serving taxpayers, SAMSAT must pay attention to environmental comfort. However, an explanation regarding the Samsat topic, especially in the public service sector. This study aims to analyze the effect of the work environment on the performance of SAMSAT employees in Maros Regency. The method used is quantitative with a descriptive approach. This research is quantitative research with a Likert scale type of questionnaire. 31 SAMSAT employees of Maros Regency were recruited as respondents. The instrument validity test uses item analysis and is calculated using the product-moment formula, while the reliability test uses Cronbach's Alpha formula. Prerequisites of analysis include normality test and linearity test. The results showed that the work environment in SAMSAT Maros Regency was in a suitable category, namely 60.22% from 100%. The results of the study indicate that the workplace environment shapes employee performance. In addition, a toxic work environment will harm employee performance and lead to work outcomes. It is more likely to be experienced by junior employees. Therefore, to overcome this problem, many strategies can be done to overcome this problem. One strategy is for organizational leaders to support employees by acknowledging their problems at work and providing essential assistance, especially for tasks with more stressful requirements.